RETINAL GANGLION CELL COMPLEX CHANGES ON OPTICAL COHERENCE TOMOGRAPHY AFTER PANRETINAL PHOTOCOAGULATION FOR TREATMENT OF PROLIFERATIV - Muhammad Shaheer (Army Medical College Rawalpindi, 2019)
Objective: To study the changes in ganglion cell complex as measured on Optical coherence tomography after panretinal photocoagulation for the treatment of diabetic retinopathy.